ANALYSIS OF SEDIMENTATION RATE AND CHARACTERISTICS OF SEABED SEDIMENT IN THE COASTAL WATERS OF TANETE RILAU DISTRICT, BARRU REGENCY - Lintang Aprilya; Amir Hamzah Muhiddin; Kamaruddin (Jurnal Ilmu Kelautan SPERMONDE, 2026)
The objective of this research is to ascertain the characteristics and sedimentation rates in the coastal waters of Tanete Rilau District. The study was conducted in March 2026 across three observation sites. Sediment data were collected utilizing the sediment trap method, which was deployed three times during the research period (at the beginning, middle, and end of the month), with each deployment lasting for two days. Seabed sediment samples were analyzed using the dry sieving method to determine the grain size distribution according to the Wentworth scale. The findings indicated that the average sedimentation rate during the observation period was 0.050 g/m²/day, with a maximum value recorded at Station 3 of 0.23 g/m²/day and a minimum value at Stations 1 and 2 of 0.01 g/m²/day. The sediment characteristics at the research site were predominantly composed of very fine sand to silt fractions, with the sediment type classified as sandy silt at Stations 1 and 2 and sand at Station 3.